Cheese : chemistry, physics, and microbiology. - Fox, P. F. (Elsevier, 2004)
The market for cheese as a food ingredient has increased rapidly in recent years and now represents upto approximately 50% of cheese production in some countries. Volume one is entitled General Aspects which will focus on general aspects on the principles of cheese science. This title contains up-to-date reviews of the literature on the chemical, biochemical, microbiological and physico-chemical aspects of cheese in general. Cheese: Chemistry, Physics, and Microbiology Two-Volume Set, 3E is available for purchase as a set, and as well, so are the volumes individually.
Previous edition: 1993.
Keywords: Cheese.; Cheese -- Varieties.; Cheese -- Microbiology.; elektronické knihy; electronic books